Efektivitas Model Pembelajaran Game Based Learning Terhadap Hasil Belajar Siswa dalam Pembelajaran Mendalam di Sekolah Dasar - Bagus Setiyono; Ahmad Ilham Asmaryadi; Wiwik Okta Susilawati (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the effect of the Game-Based Learning (GBL) instructional model on students’ science and social studies (IPAS) learning outcomes in supporting the realization of deep learning in primary education. This research employed a quantitative approach using a pre-experimental One Group Pretest–Posttest Design. The participants consisted of 18 fourth-grade students at SDN 06 Koto Baru, Dharmasraya Regency. Data were collected through multiple-choice tests and a learning questionnaire measuring deep learning dimensions, namely mindful, meaningful, and joyful learning. Data analysis was conducted using the Kolmogorov–Smirnov normality test and Paired Samples t-test. The findings indicate a significant improvement in students’ learning outcomes, with the mean pretest score increasing from 62.88 to 85.33 in the posttest. The significance value of 0.000 < 0.05 confirms that the GBL model has a statistically significant effect on IPAS learning outcomes and contributes to the implementation of deep learning in primary education.